Three new species from the Aoridae and Maeridae (Crustacea, Amphipoda) from Thai Waters - Wongkamhaeng, Koraon; Coleman, Charles Oliver; Pholpunthin, Pornsilp (Zootaxa, 2013)
Four species of amphipods from the families Aoridae and Maeridae were collected from Thai Waters in 2011. Three species, Grandidierella phetraensis sp. nov., Ceradocus andamanensis sp. nov. and Parelasmopus siamensis sp. nov. are new to science and Bemlos quadrimanus (Sivaprakasam, 1970) has not been previously reported from Thai Waters. Their characters are described and illustrated. All specimens are deposited at Princess Maha Chakri Sirindhorn Natural History Museum, Prince of Songkla University, Thailand and the Museum für Naturkunde, Berlin.